Pengaruh Blue Ecconomy terhadap Pengelolaan Keuangan di Sektor Kelautan dan Perikanan pada Kampung Nelayan Morokrembangan - Luluk Mushfiroh; Vivi Duwi Lestari; Aliatus Nurrochmah; Maria Yovita R. Pandin (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2024)
This research was conducted in Morokrembangan to determine the influence of the Blue Economy on financial management. The quantitative methodology used in this research was by distributing questionnaires to Morokrembangan fishermen. A total of 50 respondents participated in this research. To test the hypothesis, researchers conducted survey results via SPSS. The results of this test produced information that the Blue Economy provides financial management for Morokrembangan fishermen.